With a little help from my friends? How learning activities and network ties impact performance for high tech startups in incubators. (March 2021) - Sullivan, Diane M.; Marvel, Matthew R.; Wolfe, Marcus T.
Abstract: Drawing from the dynamic learning perspective of entrepreneurship, this paper investigates how entrepreneurs' learning activities and new venture performance (early sales and employee growth) are impacted by reliance on different network tie partners (strong and weak ties) for learning. Utilizing a sample of early-stage high technology ventures in incubators, we find weak ties help improve performance when utilized as a source of assistance in certain learning domains, but reduce performance when utilized as a source of help in other learning areas. The relationship between customer learning activities and employee growth is strengthened by entrepreneurs' reliance on weak ties for help with customer learning. On the other hand, the relationship between financial learning activities and employee growth is weakened by entrepreneurs' reliance on weak ties for help with financial learning. By accounting for the complex interplay between both content (domain learning activity) and process attributes (tie reliance for learning), the paper contributes by developing and testing a theoretical framework more capable of explaining the dynamics of entrepreneurial learning. Highlights: Learning content and process must be addressed in entrepreneurial learning research. Customer and financial learning are important content domains for incubator firms. Entrepreneurs' active, content-focused, learning activities improve firm outcomes. Relying on weak or strong ties for learning help impacts outcomes differently. Learning task processes with weak or strong ties depends on learning content domain.